2016
DOI: 10.18869/acadpub.jafm.68.224.24340
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Three-Dimensional Axisymmetric Unsteady Stagnation-Point Flow and Heat Transfer Impinging on an Accelerated Flat Plate

Abstract: General formulation and solution of Navier-Stokes and energy equations are sought in the study of threedimensional axisymmetric unsteady stagnation-point flow and heat transfer impinging on a flat plate when the plate is moving with variable velocity and acceleration towards the main stream or away from it. As an application, among others, this accelerated plate can be assumed as a solidification front which is being formed with variable velocity. An external fluid, along z-direction, with strain rate a imping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…For solving the algebraic system of equations, TDMA (Three Diagonal Matrix Algorithm) within ADI (Alternating Direction Implicit) method is used. In addition, the resulted velocities of momentum solution are used to obtain the exact solution of energy equation (Shokrgozar et al, 2016). However, this exact solution is not used to capture the fluid temperature in the computational domain at each time step.…”
Section: Numerical Heat Transfer Solutionmentioning
confidence: 99%
“…For solving the algebraic system of equations, TDMA (Three Diagonal Matrix Algorithm) within ADI (Alternating Direction Implicit) method is used. In addition, the resulted velocities of momentum solution are used to obtain the exact solution of energy equation (Shokrgozar et al, 2016). However, this exact solution is not used to capture the fluid temperature in the computational domain at each time step.…”
Section: Numerical Heat Transfer Solutionmentioning
confidence: 99%
“…The two-dimensional stagnation ow and heat transfer on an accelerated at plate was investigated by Shokrgozar and Rahimi [22]. Axisymmetric stagnation ow and heat transfer on an accelerated at plate was presented by Shokrgozar et al [23]. Stagnation-ow solidi cation of an inviscid uid that freezes at a common border was considered by Brattkus and Davis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Further it results in poor heat transfer coefficient due to mixing of jets before impinging on the target. Numerical simulation of three dimensional axisymmetric unsteady stagnation-point flow and heat transfer of a jet impinging on a flat plate which is moving towards the jet and away from the jet with varying velocity and acceleration has been carried out by Shokrgozar et al (2016). It is observed that the velocity of the plate is more influential on the velocity and thermal boundary layers than the acceleration of the plate.…”
Section: Introductionmentioning
confidence: 99%